Tensiometer based irrigation scheduling in wheat for improved water use efficiency in Nepal - YADAV, MATHURA; TRIPATHI, JANMEJAI; BHATT, RAJAN; RAWAL, NABIN (Journal of Soil and Water Conservation, 2020)
Delineating tensiometer based irrigation scheduling in wheat to reduce irrigations is need of present time, for which an experiment was conducted at National Wheat Research Program, Nepal during 2013- 2014 and 2014-2015. Trial was conducted with 3 levels of irrigation threshold (20, 35 and 50 kPa) and three depths of installed tensiometers (20, 35 and 50 cm) with three replications. The main objective was to evaluate the effects of tensiometer based irrigation scheduling on wheat yield. Tensiometer readings were recorded on daily basis and irrigation was applied accordingly. Data on yield and yield attributes collected and analyzed using Genstat statistical package. Compiled results delineated that, plant height, spikes m-2, grains per spikes, spike length grain yield and total biomass variables were not significantly while 1000 grain weight, harvest index variable were significantly affected during 2013-14. However, during 2014-15 all the growth and yield parameters were non-significantly affected with irrigation scheduling except harvest index based on tensiometer reading at divergent soil depths with varying potential values. The experiment concluded that two irrigations each at crown root initiation and flowering to milking stage was found optimal for wheat crop at Bhairahawa conditions of Nepal if substantial winter season rainfall is received.